Overview of Islamic Law on “Leasing” Implementationin The Indonesian Civil Code - Hasyim, A. Dardiri (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
Leasing  agreement  is  a  mixture  of  agreements  on purchasing,  selling,  and  renting.  In  leasing,  when  a  buyer  can’t  buy goods in cash, then the agreement is held in which the buyer is allowed to  repay  with  several  installments.  The  goods  will  be  owned by  the buyer by the time the installments have been paid. Duringthe payment of installments, as long as it is not paid completely, the  buyer is still a tenant. As a tenant, the buyer is only allowed to take  advantage of the goods  and  does  not  have  the  right  to  transfer  the  goods  to another person.  If  the  transfer  term  is  broken  before  the  payment  of installments is completed, then the buyer will be subjectedto criminal accusations because he/she makes the others’ property lost. Then, the leasing  agreement  here  is  likely  to  lead  to  a  form  of  a  purchase agreement rather than of a renting, for the main point is all about the transfer of property rights. The different status over the ownership of goods  will  also  have  different  legal  consequences.  In  terms  of purchase, a buyer becomes the owner of the goods, which makes him feel free to do over the things possessed, such as leasing them as rental, mortgage, and so on to another party. In terms of leasing, whereas the buyer  has  not  become  the  owner  of  the  goods,  he  could  not  act lawfully  over  them.  While  Islam  has  the  basic  law  upon  leasing agreement, it is necessary to implement this law in leasingagreement towards the Indonesia Civil Code.